Access to Justice for Women and Children in Divorce Cases in the Indonesian Religious Courts - Hotnidah Nasution; Ahmad Rifqi Muchtar (Universitas Islam Negeri Jakarta, 2020)
This research aims to investigate access to justice for children and women in the Religious Court Decisions after the issuance of Circular Letter of Supreme Court No. 4 of 2016, Point 5 on Religious Chamber. This particular point states that the Religious Court can require a father to provide child maintenance if the child is under the custody of the mother. This is a normative study, with the data obtained from interviews and 150 Religious court decisions. These decisions are issued by the Religious Courts of East Jakarta and Central Jakarta from 2015-2017. The examination of those Decisions reveals that most of the decisions on divorce do not mention any stipulation about child maintenance. This means that the Supreme Court Circular No. 4 of 2016 has not been able to protect children rights in the case of divorce, as well as women’s rights. From the court used in this study, only 14% that require the fathers to provide child maintenance after divorce. This percentage is almost similar to the decisions issued before the issuance of the Circular, which only 12% in 2016, and 14% in 2017. AbstrakPenelitian ini bertujuan untuk mengetahui akses keadilan bagi anak dan perempuan dalam Putusan Pengadilan Agama pasca terbitnya Keputusan Mahkamah Agung Nomor 4 Tahun 2016 Poin 5 tentang Kamar Beragama. Dalam poin khusus ini disebutkan bahwa Pengadilan Agama dapat meminta seorang ayah untuk mengasuh anak jika anak tersebut berada di bawah asuhan ibunya. Penelitian ini bersifat normatif, dengan data diperoleh dari wawancara dan 150 putusan Pengadilan Agama. Putusan-putusan tersebut dikeluarkan oleh Pengadilan Agama Jakarta Timur dan Jakarta Pusat dari tahun 2015- 2017. Berdasarkan pemeriksaan terhadap Putusan tersebut, sebagian besar Putusan perceraian tidak menyebutkan ketentuan tentang pengasuhan anak. Artinya, Surat Edaran Mahkamah Agung Nomor 4 Tahun 2016 belum mampu melindungi hak anak dan hal perempuan dalam kasus perceraian. Data pengadilan yang digunakan dalam penelitian ini, menyebutkan hanya 14% yang mewajibkan ayah untuk mengasuh anak setelah perceraian. Persentase ini hampir sama dengan keputusan yang dikeluarkan sebelum keluarnya keputusan tersebut, yaitu hanya 12% pada 2016, dan 14% pada 2017.